2019
DOI: 10.1172/jci127397
|View full text |Cite
|
Sign up to set email alerts
|

Residual β cell function and monogenic variants in long-duration type 1 diabetes patients

Abstract: BACKGROUND. In the Joslin Medalist Study (Medalists), we determined whether significant associations exist between β cell function and pathology and clinical characteristics. METHODS. Individuals with type 1 diabetes (T1D) for 50 or more years underwent evaluation including HLA analysis, basal and longitudinal autoantibody (AAb) status, and β cell function by a mixed-meal tolerance test (MMTT) and a hyperglycemia/ arginine clamp procedure. Postmortem analysis of pancreases from 68 Medalists was performed. Mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
89
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(100 citation statements)
references
References 48 publications
4
89
1
3
Order By: Relevance
“…In the DCCT, preserved C-peptide secretion was associated with lower rates of severe hypoglycaemia [7], fewer diabetes complications, lower HbA 1c and lower insulin doses [8], although these associations were mostly observed in the intensive treatment arm. These associations were not noted in the recent Joslin Medalist Study which assessed individuals with long-standing type 1 diabetes [5]. Preservation of C-peptide has been associated with lower self-reported rates of symptomatic, asymptomatic and severe hypoglycaemia, although not with measures of impaired awareness, in a number of observational studies [9][10][11].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In the DCCT, preserved C-peptide secretion was associated with lower rates of severe hypoglycaemia [7], fewer diabetes complications, lower HbA 1c and lower insulin doses [8], although these associations were mostly observed in the intensive treatment arm. These associations were not noted in the recent Joslin Medalist Study which assessed individuals with long-standing type 1 diabetes [5]. Preservation of C-peptide has been associated with lower self-reported rates of symptomatic, asymptomatic and severe hypoglycaemia, although not with measures of impaired awareness, in a number of observational studies [9][10][11].…”
Section: Introductionmentioning
confidence: 86%
“…Significant residual C-peptide secretion is more likely in those diagnosed in adulthood, ranging from 36% within the first 5 years to 22% up to 20 years post diagnosis [3], with evidence of stabilisation after an exponential fall in the first 7 years [4]. Even after 50 years of type 1 diabetes, 32.4% of individuals retain detectable C-peptide levels (>16 pmol/l) [5]. Evidence from the DCCT suggests that intensive therapy may prolong the duration of C-peptide persistence [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently published examples involving monogenic diabetes demonstrate how pathogenicity prediction algorithms can be very inaccurate for predicting which genetic variants are likely causal of dominant monogenic disease (1)(2)(3)(4). Here, we highlight the potential pitfalls of variant classification and how they can be avoided.…”
Section: Prediction Algorithms In Genomic Medicinementioning
confidence: 92%
“…A recent study used a bioinformatic algorithm to identify 88 "likely pathogenic" monogenic diabetes variants in 80 individuals (8.6%) from a cohort of 1019 individuals with type 1 diabetes for 50 or more years (4). Application of the widely used American College of Medical Genetics and Genomics and the Association for Molecular Pathology (ACMG/AMP) standards and guidelines (5) classifies only nine of these 88 variants as likely pathogenic or pathogenic variants that would be reported by our clinical diagnostic laboratory as likely causative of the patients' diabetes.…”
Section: Prediction Algorithms In Genomic Medicinementioning
confidence: 99%
“…Although some donors with elevated C‐peptide levels showed most numerous insulin‐positive islets, it was reported that this was not always the case, with some subjects showing solely scattered singlet/doublet cells and high values of serum C‐peptide or vice versa. These results suggest that even though the presence of insulin‐positive islets in several donors with long‐standing T1D positively correlated with pre‐mortem C‐peptide values (indicating a fully functional phenotype), the scenario is heterogeneous, and the function of residual β‐cells (both scattered and within islets) should be further studied …”
Section: Insulitis β‐Cell Loss and β‐Cell Persistence In T1dmentioning
confidence: 99%